STAKEHOLDER PERSPECTIVES ON MANAGING ABANDONED, LOST, OR DISCARDED FISHING GEAR IN REMBANG CRAB FISHERIES - Permana, Sofiyan Muji; Yulisti, Maharani; Natsir, Mohamad; Mahiswara; Baihaqi; Helman Nur Yusuf; Suryanto; Regi Fiji Anggawangsa; Iqnatius Tri Hagiyatno; Aris Budiarto; Irfan Yulianto; Budy Wiryawan (Bogor Agricultural University, 2025)
Abandoned, lost, or discarded fishing gear (ALDFG) poses a significant threat to natural marine habitats, causing damage to aquatic ecosystems and affecting fishing productivity. In this study, the Analytic Hierarchy Process (AHP) method was employed, and interviews were conducted with stakeholders to identify strategies for preventing the occurrence of ALDFG in crab fisheries in Rembang waters. The results indicate that the highest-priority criteria, as identified by stakeholders, include: marine debris: plastic bags; fishing gear waste: fishing traps; cause: entanglement with other fishing gear; impact: decreased income; solution: prohibition of modified purse seines; and actor: central government. These were considered the most significant by stakeholders. In contrast, the lowest-priority criteria were marine debris: sacks; fishing gear waste: nets or flags; cause: physical damage (cuts); impact: anxiety; solution: establishment of an oversight committee; and actor: business entities. It is hoped that these findings will offer stakeholders new insights and perspectives, which will accelerate the process of integrating diverse public opinions to develop more effective approaches to handle ALDFG. Keywords: Analytic Hierarchical Process, Abandoned, lost, or discarded fishing gear, Crab fisheries